2012
DOI: 10.1186/1472-6807-12-13
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the Yersinia enterocolitica type III secretion chaperone SycD in complex with a peptide of the minor translocator YopD

Abstract: BackgroundType III secretion systems are used by Gram-negative bacteria as “macromolecular syringes” to inject effector proteins into eukaryotic cells. Two hydrophobic proteins called translocators form the necessary pore in the host cell membrane. Both translocators depend on binding to a single chaperone in the bacterial cytoplasm to ensure their stability and efficient transport through the secretion needle. It was suggested that the conserved chaperones bind the more divergent translocators via a hexapepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 59 publications
(94 reference statements)
2
30
2
Order By: Relevance
“…Based on our structure, this assumption is incorrect. Although previous structures for IpaB-IpgC (Lunelli et al, 2009), SycD-YopD peptide (Schreiner and Niemann, 2012), and PcrH-PopD 48-55 (Job et al, 2010) concluded that the hydrophobic anchor of the translocator was bound to the concave surface of the chaperone, our structure shows that binding at the concave region is only part of the overall mechanism for the interaction. The N-terminal arm as well as the convex and top surfaces of the TPR are also equally, if not more, important for this interaction.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Based on our structure, this assumption is incorrect. Although previous structures for IpaB-IpgC (Lunelli et al, 2009), SycD-YopD peptide (Schreiner and Niemann, 2012), and PcrH-PopD 48-55 (Job et al, 2010) concluded that the hydrophobic anchor of the translocator was bound to the concave surface of the chaperone, our structure shows that binding at the concave region is only part of the overall mechanism for the interaction. The N-terminal arm as well as the convex and top surfaces of the TPR are also equally, if not more, important for this interaction.…”
Section: Discussioncontrasting
confidence: 53%
“…The N-terminal molecular anchor is conserved in both the major and minor translocators of the Ysc and Inv-Mxi-Spa families with the consensus sequence of P/VXLXXP (Discola et al, 2014;Job et al, 2010;Lunelli et al, 2009;Schreiner and Niemann, 2012) ( Figure 3D). In the structure of AcrH-AopB 40-264 , we further confirmed that this consensus sequence (VVLPQP; residues Val48 0 -Pro53 0 ) in AopB interacts in an extended conformation with the hydrophobic concave surface of AcrH ( Figure 3B).…”
Section: The Interface Between the Molecular Anchor Of Aopb And Acrhmentioning
confidence: 97%
See 1 more Smart Citation
“…LcrH protein and buffer were added to the differing denaturant concentrations to give identical protein (from 3 to 80 M) and buffer concentrations (LcrH buffer). The length of time the experiments were left to equilibrate was determined by repeating a denaturation experiment after differing equilibration times (4,8,12, and 24 h). These all gave superimposable curves, showing that equilibrium was reached after 4 h (supplemental Fig.…”
Section: Cloning Expression and Purification Of Lcrh And Truncatedmentioning
confidence: 99%
“…By solving the high resolution crystal structure of PcrH, we had also shown that it folds into seven TPR motifs that generate a concave region that is capable of binding PopD residues 49 -56 (8). Notably, IpgC, the type II chaperone of the type III secretion system of Shigella, also recognizes a short peptide of the N terminus of the major translocator molecule (50,51), and SycD from Yersinia enterocolitica was also structurally characterized in complex with a peptide from minor translocator YopD (52).…”
Section: The Exposed N Terminus Of Popb Is a Molten Globule-tomentioning
confidence: 99%